Bone repair material with bionic structure and application
By designing porous structures and specific pore size distributions in bone repair materials, and in situ mineralization using decellularized matrix templates and water-soluble calcium salt-fluoride, the diffusion and leakage of existing bone repair materials in wet environments is solved. Problem, high biocompatibility and antibacterial effects have been achieved, and bone healing and mechanical properties have been improved.
Patent Information
- Application Number
- CN202411358504.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Existing bone repair materials are prone to diffusion and leakage in wet environments, resulting in high risk of immune response and infection, lack of antibacterial effects, and the pore size distribution of the material has a great impact on mechanical and biological properties, making it difficult to achieve structural bionics.
The bone repair material using porous structure bionic has a porosity of 83-95%, a pore size distribution of 0-400um, and a pore size of 50-175um accounts for 70-95%. Water-soluble calcium salt-fluoride is added to the decellular matrix template. In situ pretreatment and phosphate mineralization growth were carried out, pore size distribution was controlled, and lyophilized cross-linked under pH=10.6-11.4 and 35-39°C to generate bone repair material with antibacterial effects.
The material is not easy to spread in a wet environment, has high biocompatibility and antibacterial effects, promotes bone healing, improves osteoblast binding and growth effects, and has self-supporting mechanical properties to avoid bone brittlement and cracks.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a structural bionic bone repair material and its application. Background Art
[0002] In natural bones, the main inorganic and organic components are hydroxyapatite and collagen respectively. Taking teeth as an example, teeth include pulp, cementum, dentin and enamel, among which the main part is dentin. Inorganic salts account for about 70% of dentin, mainly hydroxyapatite, calcium phosphate, etc., and organic matter accounts for about 30%, mainly collagen.
[0003] Patent No. CN100341588C discloses a method for preparing porous collagen composite nano-hydroxyapatite artificial bone, which comprises preparing collagen and nano-hydroxyapatite separately and then mixing them. This method is easy to control the ratio of collagen and hydroxyapatite, but can only achieve component bionics, not structural bionics. Patent No. CN114832159B records a mineralized collagen material, preparation method and application, wherein NaOH, Na 3 PO 4 The second solution consisting of glycerol was added with CaCl 2 , C 2 H 5 The first solution is composed of OH and collagen to obtain a highly mineralized collagen gel that is bionic in composition and structure. Although the literature mentions that it can be freeze-dried to obtain a block material, the material is usually in a wet environment of the human body after implantation, and the block material will still be transformed into a gel state. The gel material is prone to diffusion and leakage as a bone implant material, and the chance of causing immune response and infection is higher. At the same time, after infection after injury, acid will be produced, further affecting bone healing. The literature does not mention the pore size of the obtained gel material, and the pore size of the bone graft material has a great influence on the mechanical properties and biological properties. Summary of the invention
[0004] In order to overcome the above problems, while ensuring that the bone graft material is in a wet environment, it is not only not easy to diffuse and leak, but also has a certain antibacterial effect, and also has good osteoblast binding, biological properties of ingrowth effect and mechanical properties of self-support in a wet environment. The first aspect of the present invention provides a structural bionic bone repair material, which is a porous material with a porosity of 83-95% and a pore size distribution of 0-400um, of which the pore size of 50-175um accounts for 70-95%.
[0005] Preferably, the porosity of the bone repair material is 83-92%.
[0006] Preferably, the pore size distribution of the bone repair material is 0-350 um, wherein pore sizes of 50-175 um account for 70-95%.
[0007] Further preferably, the pore size distribution of the bone repair material is 0-350 um, wherein pore sizes of 50-175 um account for 70-90%.
[0008] As a preferred embodiment, the median pore size of the structural bionic bone repair material is 70-100 um.
[0009] Preferably, the median pore size of the bone repair material is 70-90 um.
[0010] The median pore size refers to the pore size value corresponding to the vertex of the pore size distribution spectrum, that is, the pore size of the pore with the largest number in the pore network. The median pore size is of great significance for the study of porous materials with asymmetric pore size distribution.
[0011] Green D et al. have found that for porous bone repair materials, pores of 15-50μm can induce the growth of fibrous tube tissue, pores of 50-150μm can stimulate the generation of bone-like tissue, and pores of 150-500μm can directly induce the generation of mineralized bone. In addition, although repair materials with larger pore sizes can directly stimulate the generation of mineralized bone, if only relying on the direct generation of mineralized bone, it may cause a certain degree of imbalance in the ratio of organic and inorganic substances in the bone-forming site, and the physical properties of the bone-forming site, such as the risk of cracks and brittleness, will increase, and the repair speed will also be affected. Therefore, it is necessary to control the pore size distribution in bone repair materials to a certain extent, especially the proportion of pores with smaller pore sizes (50-150μm pores), so as to control the process of bone healing. On the basis of the original defect, the induced generation behavior of bone-like tissue accounts for a larger proportion, so that the final matching of the structure of the bone-forming part is higher.
[0012] Preferably, the bulk density of the structural bionic bone repair material is 0.2-0.3 g / cm 3 .
[0013] As a preferred embodiment, the structural bionic bone repair material is obtained by adding water-soluble calcium salt-fluoride to the acellular tissue matrix (ACTM) template for in-situ pretreatment, further adding phosphate for in-situ mineralization growth, freeze-drying, cross-linking, washing and then freeze-drying again.
[0014] As a preferred embodiment, the structural bionic bone repair material is obtained by adding water-soluble calcium salt-fluoride to the ACTM template for in-situ pretreatment for 30-60 minutes, adding phosphate to carry out in-situ mineralization growth for 19-24 hours, freeze-drying, cross-linking, washing and then freeze-drying again.
[0015] As a preferred embodiment, the in-situ pretreatment is carried out in an atmosphere of pH=10.6-11.4.
[0016] Preferably, the atmosphere with pH=10.6-11.4 is adjusted by aqueous ammonia.
[0017] Generally speaking, when phosphate and calcium salt react under alkaline conditions, various products may be generated, such as hydroxyapatite, calcium hydrogen phosphate dihydrate, tricalcium phosphate, octacalcium phosphate, etc. The generated products can be controlled by controlling the pH. When pH=9-11, hydroxyapatite has the lowest solubility among various products, so the product is mainly hydroxyapatite. In the present invention, in addition to calcium salt, fluoride is introduced into the reaction system. Since the solubility of fluoroapatite is lower than that of hydroxyapatite, the reaction proceeds in the direction of decreasing solubility, generating part of fluoroapatite and hydroxide, so that the solution still maintains an alkaline environment, and the fluorine in the fluoroapatite exists in the form of ions.
[0018] During the healing process of bone tissue, once bacteria invade, acid will be produced, which will have a negative impact on healing. In order to avoid the generation of local acidic conditions, the inventor introduced fluoride into the system, which not only enhances the resistance to acid, but also has a certain antibacterial effect. However, at the same time, the introduction of fluoride may also cause damage to the bone formation site, such as the occurrence of bone brittleness, such as cracks and cracks, or even fractures.
[0019] As a preferred embodiment, the reaction temperature of the in-situ pretreatment and in-situ mineralization is 35-39°C.
[0020] Preferably, the reaction temperature of the in-situ pretreatment and in-situ mineralization is 37°C.
[0021] In order to control the porosity and pore size distribution of bone repair materials, the inventors conducted a large number of exploratory experiments and found that for the mineralization system of decellularized matrix-calcium salt-fluoride-phosphate, the temperature and pH control of the in situ pretreatment before the mineralization reaction has an important influence on the porosity and pore size distribution of the final bone repair material. By controlling the pH value of 10.6-11.4 and the in-situ pretreatment reaction temperature of 35-39°C, the porosity of the bone repair material is 83-92%, and the pore size distribution is 0-350um, of which the pore size of 50-175um accounts for 70-95%. On the basis of the in-situ pretreatment, the temperature of the in-situ mineralization reaction is further controlled to 35-39°C, which not only enhances the controllability of the above-mentioned pore size distribution, but also unexpectedly makes the repaired bone formation site less prone to cracks and discoloration, which to a certain extent indicates that it may overcome the problem of bone embrittlement caused by the introduction of fluoride. The inventors speculate that the above-mentioned control conditions affect the crystallinity and deposition behavior of hydroxyapatite, and the resulting minerals with a specific crystallinity may be more deposited on the outside of the fiber skeleton of the ACTM template, thereby making the material less prone to the mechanical phenomenon of stretching-contraction.
[0022] As a preferred embodiment, the volume mass ratio of the ACTM template and the water-soluble calcium salt-fluoride is (23-40) mL: (1.8-6.4) g.
[0023] Preferably, the water-soluble calcium salt-fluoride consists of a water-soluble calcium salt and a water-soluble fluoride.
[0024] Preferably, in the water-soluble calcium salt-fluoride, the molar mass ratio of the water-soluble calcium salt to the water-soluble fluoride is 100:(1-50).
[0025] Further preferably, in the water-soluble calcium salt-fluoride, the molar mass ratio of the water-soluble calcium salt to the water-soluble fluoride is 100:(1-15) or 100:(39-50).
[0026] Preferably, the water-soluble calcium salt is one or more of calcium nitrate, calcium acetate, calcium chloride, calcium bicarbonate or calcium citrate.
[0027] More preferably, the water-soluble calcium salt is calcium acetate.
[0028] Preferably, the water-soluble fluoride is one or more of sodium fluoride, potassium fluoride or calcium fluoride. More preferably, the water-soluble fluoride is sodium fluoride or potassium fluoride.
[0029] As a preferred embodiment, the mass ratio of the water-soluble calcium salt-fluoride to the phosphate is (2.12-2.43):1.
[0030] The phosphate is one or more of diammonium hydrogen phosphate, dipotassium hydrogen phosphate or disodium hydrogen phosphate; As a preferred embodiment, the ACTM template is a decellularized matrix slurry.
[0031] Preferably, the decellularized matrix slurry is prepared by mixing the decellularized matrix and an aqueous solution of an acidic protease.
[0032] The decellularized matrix slurry is prepared by mixing the decellularized matrix and an acidic protease aqueous solution, wherein the initial concentration of the decellularized matrix in the decellularized matrix slurry is 0.01-0.2 g / ml.
[0033] The acidic protease aqueous solution may be an acidic pepsin aqueous solution.
[0034] The process of obtaining the decellularized matrix is described in patent number CN106075583B.
[0035] The source of the acellular matrix includes at least one of the submucosal layer, basement membrane, pericardium, dermis, etc. of hollow organs such as the intestine, esophagus, stomach, etc. of humans and mammals.
[0036] The collagen contained in the decellularized matrix exists in the form of fibers, which is conducive to the adhesion, proliferation and differentiation of cells, and can promote tissue regeneration and repair. The rich fibronectin plays an adhesion role between cells and cells, cells and matrix, and plays an important role in angiogenesis and regulating the information transmission between cells and matrix. In recent years, it has been widely studied and applied in the important repair of various tissues and organs. Studies have shown that decellularized matrix biomaterials have a guiding effect on bone cells and have good biocompatibility.
[0037] Preferably, the structural bionic bone repair material is obtained by adding water-soluble calcium salt-fluoride to the ACTM template for in-situ pretreatment for 30-60 minutes, adding phosphate to carry out in-situ mineralization growth for 19-24 hours, freeze-drying, immersing in 0.1-2 mol / L cross-linking agent aqueous solution for cross-linking, washing with distilled water and then freeze-drying again.
[0038] The cross-linking agent is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) or glutaraldehyde.
[0039] The second aspect of the present invention provides a structural bionic bone repair material for use in tooth repair materials, jaw repair materials, spine repair materials, joint repair materials, and pelvic repair materials. Beneficial Effects
[0040] (1) The decellularized matrix ACTM template is bonded to hydroxyapatite at the molecular level to form a composite material, which simulates the structure and composition of natural bone tissue, facilitates the recognition of human cells and macromolecules, and improves the biological activity of the material after implantation in the body. The present invention controls the pore size distribution in the bone repair material, especially the proportion of pores with smaller pore sizes, so as to control the induced generation of bone-like tissue in the bone healing process based on the original defect, thereby making the final bone formation structure more compatible.
[0041] (2) Compared with other allogeneic bone or xenogeneic bone (decalcified bone matrix DBM) materials, the biomimetic bone repair material obtained by the present invention is less likely to cause an immune response, has high biocompatibility after implantation in the body, and has excellent bone regeneration activity.
[0042] (3) Liquids have high hygroscopicity and can better absorb endogenous growth factors and enhance osteogenic activity.
[0043] (4) The antibacterial effect of the material is improved, which further promotes bone healing. It is less likely to have cracks, fissures and discoloration. It has high mechanical strength and overcomes the problem of bone brittleness caused by the introduction of fluoride.
[0044] (5) It has good biological properties of osteoblast binding and ingrowth effect and mechanical properties of self-support in a wet environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is the structural bionic bone repair material obtained in Example 1.
[0046] Figure 2 XRD spectrum of the structural bionic bone repair material obtained in Example 1.
[0047] Figure 3 This is the infrared spectrum of the structural bionic bone repair material obtained in Example 1. DETAILED DESCRIPTION
[0048] Example 1
[0049] This example provides a structural bionic bone repair material, such as Figure 1 , by adding water-soluble calcium salt-fluoride to the ACTM template for in-situ pretreatment at 37°C, pH=11.4 (adjusted by ammonia water) for 60 minutes, and then adding phosphate. After in-situ mineralization growth at 37°C for 22 hours, it was freeze-dried and immersed in a 1.5 mol / L cross-linking agent (EDC) aqueous solution for cross-linking for 24 hours. It was washed with distilled water and then freeze-dried again to obtain.
[0050] The volume mass ratio of ACTM template and water-soluble calcium salt-fluoride is 30 mL:2.6 g.
[0051] The water-soluble calcium salt-fluoride is composed of water-soluble calcium salt and water-soluble fluoride. In the water-soluble calcium salt-fluoride, the molar mass ratio of the water-soluble calcium salt to the water-soluble fluoride is 100:15.
[0052] The mass ratio of water-soluble calcium salt-fluoride and phosphate is 2.25:1.
[0053] The water-soluble calcium salt is calcium acetate, the water-soluble fluoride is sodium fluoride, and the phosphate is diammonium hydrogen phosphate.
[0054] The ACTM template is a decellularized matrix slurry, which is prepared by mixing a decellularized matrix (derived from the submucosal layer of the porcine small intestine) and an acidic pepsin aqueous solution (purchased from Qingdao Jieshikang, a 0.4% pepsin aqueous solution). The initial concentration of the decellularized matrix in the decellularized matrix slurry is 0.02 g / ml.
[0055] The process of obtaining the decellularized matrix is described in patent number CN106075583B.
[0056] Example 2
[0057] This example provides a structural bionic bone repair material. The difference from Example 1 is that after adding water-soluble calcium salt-fluoride to the ACTM template for in-situ pretreatment at 37°C and pH=10.6 (adjusted by ammonia water) for 40 minutes, phosphate is added, and after in-situ mineralization growth at 37°C for 24 hours, the material is freeze-dried, immersed in a 1 mol / L cross-linking agent (EDC) aqueous solution for cross-linking for 24 hours, and then washed with distilled water and freeze-dried again to obtain the material.
[0058] The volume mass ratio of ACTM template and water-soluble calcium salt-fluoride is 30 mL:1.9 g. The molar mass ratio of water-soluble calcium salt and water-soluble fluoride is 100:39.
[0059] Example 3
[0060] This example provides a structural bionic bone repair material. The difference from Example 1 is that after adding water-soluble calcium salt-fluoride to the ACTM template for in-situ pretreatment at 37°C and pH=11 (adjusted by ammonia water) for 60 minutes, phosphate is added, and after in-situ mineralization growth at 37°C for 21 hours, the material is freeze-dried, immersed in a 0.8 mol / L cross-linking agent (EDC) aqueous solution for cross-linking for 24 hours, and then washed with distilled water and freeze-dried again to obtain the material.
[0061] The volume mass ratio of ACTM template and water-soluble calcium salt-fluoride is 40mL:4.1g.
[0062] The mass ratio of water-soluble calcium salt-fluoride and phosphate is 2.36:1.
[0063] Comparative Example 1 This example provides a structural bionic bone repair material. The difference from Example 1 is that after adding water-soluble calcium salt-fluoride to the ACTM template for in-situ pretreatment at 39°C and pH=9 (adjusted by ammonia water) for 50 minutes, phosphate is added, and after in-situ mineralization growth at 37°C for 24 hours, the material is freeze-dried, immersed in a 1 mol / L cross-linking agent (EDC) aqueous solution for cross-linking for 24 hours, and then washed with distilled water and freeze-dried again to obtain the material.
[0064] Comparative Example 2 This example provides a structural bionic bone repair material. The difference from Example 1 is that after adding water-soluble calcium salt-fluoride to the ACTM template for in-situ pretreatment at 25°C and pH=11 (adjusted by ammonia water) for 60 minutes, phosphate is added, and after in-situ mineralization growth at 25°C for 24 hours, the material is freeze-dried, immersed in a 1 mol / L cross-linking agent (EDC) aqueous solution for cross-linking for 24 hours, and then washed with distilled water and freeze-dried again to obtain the material.
[0065] Comparative Example 3 This example provides a structural bionic bone repair material. The difference from Example 1 is that the volume mass ratio of the ACTM template and the water-soluble calcium salt-fluoride is 30 mL:1.3 g, and the molar mass ratio of the water-soluble calcium salt and the water-soluble fluoride in the water-soluble calcium salt-fluoride is 100:8.
[0066] The mass ratio of water-soluble calcium salt-fluoride and phosphate is 2.12:1.
[0067] Comparative Example 4 This example provides a structural bionic bone repair material. The difference from Example 1 is that the volume mass ratio of the ACTM template and the water-soluble calcium salt-fluoride is 35 mL:3.2 g, and the molar mass ratio of the water-soluble calcium salt and the water-soluble fluoride in the water-soluble calcium salt-fluoride is 100:9.
[0068] The mass ratio of water-soluble calcium salt-fluoride and phosphate is 1.73:1.
[0069] Comparative Example 5 This example provides a structural bionic bone repair material. The difference from Example 3 is that the volume mass ratio of the ACTM template and the water-soluble calcium salt-fluoride is 40 mL:5.3 g, and in the water-soluble calcium salt-fluoride, the molar mass ratio of the water-soluble calcium salt and the water-soluble fluoride is 100:20.
[0070] The mass ratio of water-soluble calcium salt-fluoride and phosphate is 2.79:1.
[0071] Comparative Example 6 This example provides a structural bionic bone repair material. The difference from Example 1 is that after adding water-soluble calcium salt-fluoride to the ACTM template for in-situ pretreatment at 37°C and pH=11.4 (adjusted by ammonia water) for 60 minutes, phosphate is added, and after in-situ mineralization growth at 37°C for 22 hours, the material is washed with distilled water and freeze-dried to obtain the material.
[0072] The results showed that the uncrosslinked sample obtained in this example had a loose macroscopic structure and was not easy to shape when observed with the naked eye.
[0073] Performance Testing 1. Porosity, pore size distribution and material bulk density test: The porosity of the structural bionic bone repair materials obtained in Examples 1-3 and Comparative Examples 1-5 was tested using the drainage method, and the results are shown in Table 1. The pore size distribution of the materials was tested using a V-Sorb X800 (DM) dual-module multifunctional specific surface area and pore size analyzer, and the results are shown in Table 1. The bulk density of the materials was tested in accordance with GB / T-1966, and the results are shown in Table 1.
[0074] Table 1
[0075] The bulk density can reflect the compactness of the material. A high bulk density means that the molecules are arranged more closely, and its mechanical properties will be better, but its flexibility will also decrease. For bone repair materials, if the bulk density is too high, it is difficult for tissue cells to grow in, and if the bulk density is too low, its mechanical support performance is poor.
[0076] 2. XRD Characterization: The structural bionic bone repair material obtained in Example 1 was subjected to X-ray diffraction test. The results are as follows: Figure 2 As can be seen from the figure, there are two diffraction peaks, with a first characteristic single peak at 2θ=25-27° (consistent with the characteristic peak of fluorine-based apatite standard), and a second characteristic single peak at 2θ=31-33° (consistent with the characteristic peak of hydroxyapatite standard). In addition, according to the patent record of patent No. JP5553396B2, the peak of 2θ=31-35° is completely separated into four peaks, indicating that the crystallinity of the crystals formed by hydroxyapatite is high, and the lower the peak overlap here, the lower its crystallinity, and tends to be amorphous, and the hydroxyapatite with lower crystallinity helps to improve the osteogenesis efficiency, and its surface is rougher, which is conducive to the adhesion of cells, but there may be a problem that degradation is too fast and causes its final bone repair effect to be poor. While ensuring the osteogenesis efficiency in the present invention, the phenomenon of poor osteogenesis repair effect does not occur.
[0077] 3. Infrared test: The structural bionic bone repair material obtained in Example 1 was subjected to infrared test. Figure 3The upper line graph in the figure shows the infrared spectrum of the structural bionic bone repair material obtained in Example 1, and the lower line graph in the figure shows the standard infrared spectrum of the decellularized matrix of the small intestinal submucosal layer (SIS). It can be seen from the figure that the intensity of the peak belonging to the amide bond in the spectrum of the sample in Example 1 is weakening, indicating that chemical bonding occurs between hydroxyapatite and SIS, and hydroxyapatite grows in situ on SIS rather than physically compounded.
[0078] 4. Hydrophilicity test: The surface hydrophilicity of the materials obtained in Examples 1-3 and Comparative Examples 1-6 was determined by dye adsorption method using the hydrophilic dye Nile Blue (NB). The results showed that the hydrophilicity of the materials in Examples 1-3 was significantly greater than that of the samples in Comparative Examples 1-5. Good hydrophilicity indicates that the diffusion and leakage of the material in a wet environment may be reduced.
[0079] 5. Wet self-supporting performance test: The bone repair materials obtained in Examples 1-3 and Comparative Examples 1-5 were placed at 37°C and saturated humidity. After 6 hours, they were compressed to 50% in height using a universal testing machine at a compression rate of 15 mm / min for 100 cycles. The compression strengths were tested when they were compressed to 50%. The higher the compression strength, the better the wet self-supporting performance. The results are shown in Table 2.
[0080] Table 2 Example Compression strength (MPa) Example 1 16.2 Example 2 14.1 Example 3 16.8 Comparative Example 1 6.9 Comparative Example 2 5.1 Comparative Example 3 4.5 Comparative Example 4 2.1 Comparative Example 5 2.7 6. Antibacterial properties: Staphylococcus aureus and Streptococcus mutans (Streptococcus mutans is one of the main components of dental plaque and the main pathogenic bacteria of dental caries) were used to test the antibacterial properties of the bone repair materials obtained in Examples 1-3 and Comparative Examples 1-5 by the antibacterial ring method. 70 μL of bacterial suspension (1×10 8 CFU / mL) was spread on an LB agar plate, sterile gauze and the bone repair materials obtained in Examples 1-3 and Comparative Examples 1-5 were placed on the agar surface, and incubated at 37°C for 24 hours. The diameter of the inhibition ring was measured. The larger the diameter of the inhibition ring, the higher the antibacterial property. The results are shown in Table 3. Then, the incubation was continued for 7 days to observe whether cracks appeared in the bone repair material and whether the color turned yellow. The results are shown in Table 4.
[0081] Table 3 Example Staphylococcus aureus inhibition zone diameter (mm) Diameter of inhibition zone of Streptococcus mutans (mm) Example 1 19 8 Example 2 21 7 Example 3 17 7 Comparative Example 1 7 4 Comparative Example 2 5 4 Comparative Example 3 9 1 Comparative Example 4 5 2 Comparative Example 5 8 3 Table 4 Example Appearance of the material after 7 days of incubation after antibacterial performance test Example 1 No cracks, no yellowing Example 2 No cracks, no yellowing Example 3 No cracks, no yellowing Comparative Example 1 No cracks, yellowing Comparative Example 2 Cracks appear, but the color does not turn yellow Comparative Example 3 No cracks, no yellowing Comparative Example 4 Cracks appear and the color turns yellow Comparative Example 5 Cracks appear and the color turns yellow
Claims
1. A structural bionic bone repair material, wherein the structural bionic bone repair material is a porous material, It is characterized in that The porosity of the structural bionic bone repair material is 83-95%, and the pore size distribution is 0-400um, of which the pore size of 50-175um accounts for 70-95%.
2. The structural bionic bone repair material according to claim 1, It is characterized in that The median pore size of the structural bionic bone repair material is 70-100 um.
3. The structural bionic bone repair material according to claim 1 or 2, It is characterized in that The structural bionic bone repair material is obtained by adding water-soluble calcium salt-fluoride to the ACTM template for in-situ pretreatment, then adding phosphate for in-situ mineralization growth, freeze-drying, cross-linking, washing and then freeze-drying again.
4. The structural bionic bone repair material according to claim 3, It is characterized in that The structural bionic bone repair material is obtained by adding water-soluble calcium and water-soluble fluorine to the ACTM template for in-situ pretreatment for 30-60 minutes, adding phosphate to carry out in-situ mineralization growth for 19-24 hours, freeze-drying, cross-linking, washing and then freeze-drying again.
5. The structural bionic bone repair material according to claim 3, It is characterized in that The in-situ pretreatment is carried out in an atmosphere of pH=10.6-11.
4.
6. The structural bionic bone repair material according to claim 3, It is characterized in that The reaction temperature of the in-situ pretreatment and in-situ mineralization is 35-39°C.
7. The structural bionic bone repair material according to claim 3, It is characterized in that The volume mass ratio of the ACTM template and the water-soluble calcium salt-fluoride is (23-40) mL: (1.8-6.4) g.
8. The structural bionic bone repair material according to claim 3, It is characterized in that The mass ratio of the water-soluble calcium salt-fluoride to the phosphate is (2.12-2.43):
1.
9. The structural bionic bone repair material according to any one of claims 3 to 8, It is characterized in that The ACTM template is a decellularized matrix slurry.
10. Application of the structural bionic bone repair material according to claim 1 in tooth repair materials, jaw repair materials, spine repair materials, joint repair materials, and pelvic repair materials.
Citation Information
Patent Citations
Preparation method of nano-fluorapatite biomaterial
CN105271160A
Bionic artificial bone and preparation method thereof
CN110339399A
Synthetic mineralized collagen bone plug and preparation method thereof
CN114404669A
Preparation method and application of anti-inflammatory osteogenesis-promoting mineralized collagen material
CN114470332A
Biomimetic mineralized dental bone meal and preparation method thereof
CN117122741A
